2019
DOI: 10.4103/jrpp.jrpp_19_67
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hospital pharmacist counseling on clinical outcomes of type 2 diabetes mellitus outpatients

Abstract: Objective:In Indonesia, the role of a hospital pharmacist in pharmaceutical care is still limited or even absent. This study aimed to determine whether counseling by a pharmacist could improve medication adherence, controlling the glycemic status, lipid profile, and blood pressure of type 2 diabetes mellitus (T2DM) outpatients.Methods:We conducted an interventional study at RSUD Kota Depok, a secondary public hospital, Indonesia, from April to October 2018. Counseling was given three times during the 4-month s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
(16 reference statements)
2
3
0
1
Order By: Relevance
“…Similar to our findings, numbers of previously reported studies have suggested that pharmacist managed diabetes mellitus care could improve LDL-C, HDL-C, TG and cholesterol levels 16,[23][24][25][29][30][31][32] . The proportion of patients who achieved target LDL-C values (<100mg/dl) and HDL-C (40mg/dL) in our study is in agreement with the study reported by Ali et al 25 , Mourao et al 17 , Wishah et al 18 , Al Mazroui et al, 20 and Hening et al, 33 . Analysis of UKPDS data by Turner et al indicated that the risk of either angina pectoris or myocardial infarction increases by 1.57 for every 1 mmol/L increase in LDL-C level, and patients with LDL-C levels higher than 3.9 mmol/L were 2.3 times as likely to develop coronary artery disease than those with LDL-C levels less than 3 mmol/L 34 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar to our findings, numbers of previously reported studies have suggested that pharmacist managed diabetes mellitus care could improve LDL-C, HDL-C, TG and cholesterol levels 16,[23][24][25][29][30][31][32] . The proportion of patients who achieved target LDL-C values (<100mg/dl) and HDL-C (40mg/dL) in our study is in agreement with the study reported by Ali et al 25 , Mourao et al 17 , Wishah et al 18 , Al Mazroui et al, 20 and Hening et al, 33 . Analysis of UKPDS data by Turner et al indicated that the risk of either angina pectoris or myocardial infarction increases by 1.57 for every 1 mmol/L increase in LDL-C level, and patients with LDL-C levels higher than 3.9 mmol/L were 2.3 times as likely to develop coronary artery disease than those with LDL-C levels less than 3 mmol/L 34 .…”
Section: Discussionsupporting
confidence: 93%
“…Similar to our findings, numbers of previously reported studies have suggested that pharmacist managed diabetes mellitus care could improve LDL-C, HDL-C, TG and cholesterol levels 16 , 23 25 , 29 32 . The proportion of patients who achieved target LDL-C values (<100mg/dl) and HDL-C (40mg/dL) in our study is in agreement with the study reported by Ali et al 25 , Mourao et al 17 , Wishah et al 18 , Al Mazroui et al, 20 and Hening et al, 33 .…”
Section: Discussionsupporting
confidence: 93%
“… 18 Compliance in taking medication will affect drug levels in the blood and the ability to maintain a constant blood-sugar level, blood pressure, and lipid profile. 19 Based on medication-adherence measurement using the pill-counting method and the MAQ questionnaire, we found that our study subjects showed relatively high compliance, thus providing a fairly robust sample in which to analyze therapeutic effectiveness.…”
Section: Discussionmentioning
confidence: 83%
“…They found that BGL and HbA1C improved significantly in the intervention group compared to those without intervention (p<0.001). 14 A more recent pre and post cohort study undertaken on T2DM patients in Sakaka, Saudi Arabia period April to October 2021 also argued that pharmacist-based intervention significantly improved HbA1C of the T2DM patients (p<0.05). 15 The present study was limited by the relatively small sample size and short study period.…”
Section: Discussionmentioning
confidence: 99%